An analysis of the factors affecting strengthening in carbon fiber reinforced magnesium composites. (1st February 2019) - Qi, Lehua; Li, Shaolin; Zhang, Ting; Zhou, Jiming; Li, Hejun
Abstract: For a thorough understanding of strengthening of carbon fiber reinforced magnesium matrix composites (Cf /Mg composites), all the issues affecting strengthening, including interface, fibers and matrix, are comprehensively analyzed. Cf /Mg composites with different fiber and matrix composition are fabricated by liquid-solid extrusion and vacuum pressure infiltration technique in order to study the strengthening behavior. It is found that interface between fiber and matrix is critical for the strengthening of the composite. The interface are modified by either fiber coating or matrix alloying. The wettability between fiber and matrix are improved without interfacial reaction accordingly. The coated fiber are intact without structural damage after fabrication, which is in favor of reinforcement. The fine and uniform precipitates, as well as the nanocrystalline in matrix, are benefit to the enhancing of the composite. The factors affecting strengthening of Cf /Mg composites, including interface, fiber and matrix, are influenced by fiber coating, matrix alloy and fabrication process. The calculation of theoretical strength of 2D-Cf /Mg composites is also proposed in this paper. The analysis presented here are expected to be helpful in the future design and application of high strength Cf /Mg composites.